Penerapan Metode Deduktif dan Induktif dalam Manajemen - Marnis Wanji; Muhammad Firmansyah; Devira Restika Salsa Bila Gulo; Zaini Nurasa Azzahra; Siti Mujiatun (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses the application of deductive and inductive methods in management, which are relevant in facing modern business challenges. Deductive methods, which move from general principles to specific cases, are used to confirm decisions based on established theories, whereas inductive methods, which move from specific observations to generalizations, allow the formation of new theories based on empirical data. These two methods have complementary advantages and disadvantages; deductive excels in efficiency and systematic logic, but is limited to initial premises, while inductive offers flexibility in understanding complex situations, although it risks producing less valid generalizations. The integration of deductive and inductive methods can provide a holistic approach, helping organizations make decisions that are evidence-based, adaptive, and relevant to specific contexts